PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA PT. HPAI (Herbal Penawar Alwahida Indonesia)Cabang Pekanbaru - Ayu Eka Saputri; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to determine the effect of product quality and price on customer loyalty at PT. HPP (Herbal Penawar Alwahida Indonesia) Pekanbaru Branch. The type of research used is Accedental Sampling, ie anyone who accidentally meets with the researcher can be used as a sample, and determining the number of samples used the Slovin formula. The number of samples used in this study were 100 respondents who had made a purchase of PT.HPAI (Herbal Penawar Alwahida Indonesia) Pekanbaru Branch. By using data collection techniques using questionnaires and interviews. Data analysis methods used were validity test, reliability test, correlation coefficient (R), regression test, coefficient of determination (R2), significance of t test and F test. The results of this study showed that the product quality and price variables each had an influence significant, strong enough and positive to customer loyalty. Two variables have been tested in stages and together show the results that the variables of product quality and price simultaneously have a strong enough relationship to the variable customer loyalty. The amount of contribution owned by the product quality variable is greater than the magnitude of the contribution owned by the price, the coefficient of determination (R²) for the product quality variable is 38.7% and the price is 37.9%. Suggestions that can be taken regarding product prices, PT. HPAI adjusts to the prices of similar products circulating in the market and the difference between agent prices and consumer prices should not be too large. Keywords: Product Quality, Price, Customer Loyalty.